Optimal strategies for the diagnosis of community‐onset diarrhea in solid organ transplant recipients: Less is more. Issue 2 (16th March 2017) - Trinh, Sonya A.; Echenique, Ignacio A.; Penugonda, Sudhir; Angarone, Michael P.
Abstract: Background: Diarrhea, a common complication after solid organ transplant (SOT), is associated with allograft failure and death. No evidence‐based guidelines exist for the evaluation of diarrhea in SOT recipients. We performed a cost analysis to derive a testing algorithm for the diagnosis of community‐onset diarrhea that minimizes costs without compromising diagnostic yields. Design: A cost analysis was performed on a retrospective cohort of 422 SOT admissions for community‐onset diarrhea over an 18‐month period. A stepwise testing model was applied on a population level to assess test costs relative to diagnostic yields. Results: Over an 18‐month period, 1564 diagnostic tests were performed and 127 (8.1%) returned positive. Diagnostic testing accounted for 95 625 of hospital costs. The tests with the lowest cost per decrease in the false‐omission rate (FOR) were stool Clostridium difficile polymerase chain reaction (PCR) (156), serum cytomegalovirus quantitative PCR (1529), stool norovirus (NV) PCR (4673), and stool culture (6804). A time‐to‐event analysis found no significant difference in the length of hospital stay between patients with and without NV testing ( P =.520). Conclusions: A stepwise testing strategy can reduce costs without compromising diagnostic yields. In the first‐stage testing, we recommend assessment for C. difficile, cytomegalovirus, and food‐borne bacterial pathogens. For persistent diarrheal episodes, second‐stage evaluation should include stool NV PCR, Giardia / Cryptosporidium enzyme immunoassay, stool ova and parasite, reductions in immunosuppressive therapy, and possibly endoscopy. Although NV testing had a relatively low cost per FOR, we recommend NV testing during second‐stage evaluation, as an NV diagnosis may not lead to changes in clinical management or further reductions in length of hospital stay.